GGA＋U study of the electronic energy bands and state density of the wurtzite In1-xGaxN - 王伟华 赵国忠 粱希侠 (中国物理B：英文版, 2013)
The electronic band structures, densities of states （DOSs）, and projected densities of states （PDOSs） of the wurtzite In1-xGaxN with x=0, 0.0625, 0.125 are studied using the generalized-gradient approximation （GGA） and GGA＋U in density functional theory. Our calculations suggest that in the case of wurtzite InN it is important to apply an on-site Hubbard correction to both the d states of indium and the p states of nitrogen in order to recover the correct energy level symmetry and obtain a reliable description of the InN band structure. The method is used to study the electronic properties of the wurtzite In1-xGaxN. The conduction band minimum （CBM） energy increases, while the valence band maximum （VBM） energy decreases with the increase of the gallium concentration. The effect leads to broadening the band gap （BG） and the valence band width （VBW）. Furthermore, the compressive strain in the crystal can cause the BG and the VBW to increase with the increase of gallium concentrations.